Suicide by self-inflicted stab wound to the heart: a rare case of suicide from Nepal - Jha, S; Parajuli, SR; Subedi, ND (Journal of College of Medical Sciences-Nepal, 2015)
Suicide, or the deliberate act of killing oneself, accounts for a substantial number of unnatural deaths each year in many countries. Though death by self-stabbing is quite uncommon, the left part of the chest represents one of the elected sites of self-inflicted wounds because of the knowledge of the situation of the heart and that the injuries to the heart are severe. We present a case of suicidal stab to the left thoracic region involving the heart. DOI: http://dx.doi.org/10.3126/jcmsn.v10i2.12952 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(2); 33-35